Значення інформаційно-енергетичної теорії і основні перспективи її використання в інтродукції рослин - Bulakh, P.E. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
The role and importance of information-energetic theory in plant introduction and adjacenting branches of science are considered.